Effects of fishing and environmental parameters on the commercial bony fish assemblage in the southern Caspian Sea - Fazli Hasan; Kaymaram Farhad; Daryanabard Gholam Reza (Oceanological and Hydrobiological Studies)
Since the 1990s, anthropogenic activities have been the major direct or indirect threats to the structural and functional organization of the unique ecosystem of the Caspian Sea (CS). This study attempts to investigate the relationships between fish community structure and environmental parameters and to analyze the Abundance Biomass Comparison (ABC) in the CS. The input data, including catch data by species and environmental parameters, were collected from 1996 to 2017. Of the 13 bony fish species identified, only two species Rutilus kutum and Chelon aurata accounted for 47.14% and 62.65%, and 40.80% and 29.34% of CPUE and NPUE, respectively. DisTLM revealed that five environmental variables showed a significant linear relationship with the NPUE resemblance matrix. Based on the AIC criteria, the combination of year, precipitation, SST_Apr, SSL, SST, GTA, Iranian rivers, and Volga discharges explain 80.3% of the total variability. Based on the ABC curves and W statistics, it was concluded that the fish assemblage was environmentally stressed from 1996 to 2003. The Shannon diversity index (H′) showed a decreasing trend, suggesting that fish species have been exposed to increasing stress over the past 22 years. Considering the current environmental conditions (downward trend in SSL river discharge and increase in SST) and anthropogenic activities, it appears that the downward trend will continue in the future.